Characteristics and effects of school based physical activity programs for schoolchildren with autism spec-trum disorder: A scoping review - Alejandra Robles; Camila Gallegos-Abello; Natalia Ulloa-Campos; Marcela Cabrera-Castillo; Rafael Zapata-Lamana; Andrea Tapia; Daniel Reyes-Molina; Mapy Chavez-Askins; Constanza Ortiz; Igor Cigarroa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Although benefits have been reported from the practice of physical activity in children with autism spectrum disorder (ASD), to a lesser extent the characteristics of the programs carried out in the school context and their effects on health are known. The objective of this review was to characterize school based physical activity programs and their effects on the health of schoolchildren with ASD. The review was carried out in accordance with the PRISMA statement in the databases, Medline and PsycINFO, between the years 2010 to 2023. A total of 20 articles were analyzed. A total sample of 683 schoolchildren with ASD (x̄=10.5 years and 73.1% male) were included. Schoolchildren with ASD had 98.1% adherence to the programs. The school based physical activity programs were mainly based on aerobic exercises, such as walking, jogging, running, and cycling (45% of the articles) with a duration between 10-16 weeks (55% of the articles), with a frequency of 2-3 times a week (60% of the articles) and with 60-minute sessions (45%). On the other hand, the most studied variables were language and motor skills (60% of the articles) and psychosocial and cognitive function (50% of the articles); together with the variables of physical and nutritional activity, these were where a higher percentage of articles with positive effects were found. The findings suggest a profile of schoolchildren with ASD and the main characteristics of school based physical activity programs in schoolchildren with ASD in terms of their extension, frequency, duration, intensity, location and provider as well as the variables most frequently evaluated and with the greatest positive effects.